High-Precision Digital Rotary Encoder Based on Dot-Matrix Gratings - Yi-Cheng Chen; Chi-Hung Lee; Ming-Jie Chou; Sheng-Chih Shen (IEEE Photonics Journal, 2018)
In this paper, a high-precision digital rotary encoder based on dot-matrix gratings (DMGs) is proposed for detecting shaft rotation. The DMG-based encoder is composed of a laser diode, a beam-shaping lens, a code disc, and a detector. In principle, a shaped rectangular beam illuminates a stripe of DMGs on the disc, and from the distribution of diffractive spots on the detector, the position of rotation is then decoded. Compared with a conventional geometric rotary encoder, this diffractive rotary encoder can achieve a fourfold resolution improvement.